Geochemical features of the Lower Silurian strata in Xiushan, Chongqing: Implications for paleoclimate reconstruction - Zhang, La; Chen, Yang; Luan, Jinhua; Zhang, Ruigang; Cui, Zhiwei; Zhao, Haitong; Wang, Qian (Journal of Asian Earth Sciences: X, 2025)
•Faunal and morphological diversity are recorded in the Lower Silurian in Chongqing.•The climate remained relatively warm during the Early Silurian.•Moderate climate may have facilitated the evolution of the early gnathostomes. The Silurian was featured by frequent climatic and environmental changes. Impoverished marine faunas slowly recovered from the end-Ordovician mass extinction. Diverse fossils have been reported from the Lower Silurian strata in Xiushan, Chongqing, southwest China, revealing a previously unrecognized diversification of jawed vertebrates in the Early Silurian. However, the paleoclimatic evolution during this period and the geochemical features of these strata are ambiguous. To reconstruct the Early Silurian paleoclimatic evolution, we have collected samples from the Lower Silurian (Xiaoheba, Rongxi, Xiushan, and Huixingshao formations) and Upper Silurian (Xiaoheba formation) strata in the Xiushan area. These Lower Silurian strata have a similar felsic source with insignificant sorting and recycling during deposition as documented by TiO2/Zr, La/Yb, Th/Sc, Zr/Sc, Cr/Th ratios, and ICV. The parent rocks of the Xiaoxi formation are complex and have been affected by recycled sediments. Weathering indices (CIAcorr, PIAcorr, WIPcorr, and CIW) of the Lower Silurian vary within the range of moderate weathering, indicating that although there are small-scale climatic changes, the climate remained relatively stable from the Aeronian to the middle-late Telychian, generally characterized by a warm environment, except for a cooler interval during the early Telychian. Combined with the report of the Chongqing Lagerstätte and various fossils in this area, we speculate that a relatively stable climate and abundant terrestrial nutrient influx may have facilitated the evolution of the early gnathostomes in the Early Silurian.